MeghRaj – A Cloud Environment for e-governance in India - Srivastava, Nidhi (International Journal of Computer Sciences and Engineering, 2025)
E-governance uses Information and communication technology for delivery of services to the citizens. Today the Government of India has adopted e-governance and many projects and services are available online for the easy delivery of the facilities to the general citizens. The e-governance has helped in increasing transparency, reducing corruption, better administration and effective interaction with the Government. Cloud computing is a new technology in which the user pays only for the service which they are using. It is economical, scalable and more secure than the current technology. Realizing this Government is making an effort to incorporate cloud computing in e-governance. This paper explains the importance of cloud computing in e-governance and briefly describes the various projects available online which are using the cloud services. Some of such projects are digilocker, online registration services, etc. Although many of these services are not fully functional but efforts are being made to implement them properly. The Government needs to take proper care while implementing cloud services keeping in mind the proper guidelines and policies so that the confidential, personal and sensitive data is safe and secure.